Identification of Functional Cell Groups in the Abducens Nucleus of Monkey and Human by Perineuronal Nets and Choline Acetyltransferase Immunolabeling - Anja K. E. Horn; Anja K. E. Horn; Annie Horng; Norbert Buresch; Ahmed Messoudi; Wolfgang Härtig (Frontiers Media S.A., 2018)
The abducens nucleus (nVI) contains several functional cell groups: motoneurons of the singly-innervated twitch muscle fibers (SIF) and those of the multiply-innervated muscle fibers (MIF) of the lateral rectus muscle (LR), internuclear neurons (INTs) projecting to the contralateral oculomotor nucleus (nIII) and paramedian tract-neurons (PMT) that receive input from premotor neurons of the oculomotor system and project to the floccular region. In monkey, these cell populations can be delineated by their chemical signature. For correlative clinico-pathological studies the identification of the homologous cell groups in the human nVI are required. In this study, we plotted the distribution of these populations in monkey nVI by combined tract-tracing and immunohistochemical staining facilitating the identification of homologous cell groups in man. Paraffin sections of two Rhesus monkeys fixed with 4% paraformaldhehyde and immunostained with antibodies directed against choline acetyltransferase (ChAT) as marker enzyme for cholinergic neurons and chondroitin sulfate proteoglycan (CSPG) to detect perineuronal nets (PNs) revealed four neuron populations in nVI with different chemical signatures: ChAT-positive and CSPG-positive SIF motoneurons, ChAT-positive, but CSPG-negative MIF motoneurons, and ChAT-negative neurons with prominent PNs that were considered as INTs. This was confirmed by combined immunofluorescence labeling of cholera toxin subunit B (CTB) or wheat germ agglutinin (WGA) and ChAT or CSPG in nVI sections from cases with tracer injections into nIII. In the rostral part of nVI and at its medial border, populations of ChAT-negative groups with weak CSPG-staining, but with strong acetylcholinesterase (AChE) activity, were identified as PMT cell groups by correlating them with the location of anterograde tracer labeling from INTs in nIII. Applying ChAT- and CSPG-immunostaining as well as AChE staining to human brainstem sections four neuron groups with the same chemical signature as those in monkey could be identified in and around the nVI in human. In conclusion, the distribution of nVI neuron populations was identified in human based on findings in monkey utilizing their markers for cholinergic neurons and their different ensheathment by PNs of the extracellular matrix.